Dissociation of water, reduction of inorganic carbon and fixation of nitrogen by siderite in sunlight - Bahadur, K.; Ranganyaki, S.; Verma, P.; Kuma, S. (1984)
Siderite has been found to dissociate water molecules, reduce inorganic carbon and fix molecular nitrogen to ammoniacal nitrogen in sunlight.